Students' Perception of The Use of English Slang Words In “Diary of a Wimpy Kid” Movie to Improve Vocabulary - Budiarti, Hardiana (English Education Journal, 2024)
Along with the times, language changes and has many varieties. There are many varieties of language development used in everyday life. One of these language varieties is slang. This study focuses on students' perceptions of the use of English slang words in the movie